2022
DOI: 10.1002/fsn3.2777
|View full text |Cite
|
Sign up to set email alerts
|

Tamjanika, a Balkan native variety of Vitis vinifera L.: Chemical characterization, antibacterial, and anti‐dermatomycosis potential of seed oil

Abstract: This study was designed to explore functional food properties of edible seed oil obtained from Tamjanika seeds—autochthonous grape variety of Balkan Peninsula. In order to accomplish our goals, seed oil was isolated by Soxhlet apparatus and chemically characterized regarding fatty acids, carotenoids, tocopherols, and tocotrienols. Antimicrobial activity of the isolated oil was tested by microdilution method. For that purposes, six bacterial species were used, belonging to human infectious agents and food conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is an old Serbian variety, characteristic of the eastern part of the country, and to the best of our knowledge, this variety has not been explored in the past. One very recent study found Tamjanika seeds as a good source of carotenoids and tocopherols [ 55 ]. Given that they are known antioxidant substances, this can be a potential explanation for our result regarding the biopotential of Black Tamjanika—autochthonous variety.…”
Section: Resultsmentioning
confidence: 99%
“…It is an old Serbian variety, characteristic of the eastern part of the country, and to the best of our knowledge, this variety has not been explored in the past. One very recent study found Tamjanika seeds as a good source of carotenoids and tocopherols [ 55 ]. Given that they are known antioxidant substances, this can be a potential explanation for our result regarding the biopotential of Black Tamjanika—autochthonous variety.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the tocotrienols content is higher compared with tocopherols. Tocotrienols outnumbered tocopherols by a factor greater than ten in the study conducted by Nikoleta Đorđevski, which examined the oil extracted using Soxhlet method from the kernels of Tamjanika, a native variety of Vitis vinifera L. found in the Balkans [ 45 ]. The most prevalent tocotrienol was γ-tocotrienol, with a concentration of 23.74 mg/100 g. In 2020 Ustun Argon et al noted that the forms of α-tocotrienol and γ-tocotrienol represent the most prevalent tocotrienols and that these two elements differ most amongst grape varieties [ 57 ].…”
Section: Phytochemical Composition Of Grape Seedsmentioning
confidence: 99%
“…Albert Lavallée (Royal) seeds during seed development. Tocopherols and tocotrienols can both be produced by this species, which is why it was chosen [ 45 , 56 ]. Here, it is demonstrated for the first time that tocopherol and tocotrienol distribution and accumulation kinetics during seed evolution considerably differ from one another.…”
Section: Phytochemical Composition Of Grape Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of V. vinifera seeds comprises 90% unsaturated fatty acids, with the major ones being linoleic fatty acid (65-75%) and oleic fatty acid (20-40%), and 10% saturated fatty acids [8,9], flavonoids (59.7 g/100 g), catechins (414 mg/100 g), procyanidins (2.5 g/100 g), phenolic compounds (73 µg/100 g) and tannins (14 mg CE/100 g); thus, they have antioxidant activity (1390.6 mMT/100 g) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%